Access to Justice for Indigenous Peoples In International Law - Wardana, IG Agung Made (UI Scholars Hub, 2012)
The status and rights of indigenous peoples have been recognized by international law. However, there remains debatable whether or not such recognition has been translated into providing access to justice to such peoples when their rights are violated. Therefore, the research has been conducted to examine the extent to which international law allowing access to justice for indigenous peoples given that state remains the dominant subject in international law and in some countries the state itself seems to be reluctant to recognize the status and rights of indigenous peoples in its territory. It shows that several mechanisms can be used by indigenous peoples under the international legal system in the context of access to justice although they are argued to be insufficient in securing the status and rights of indigenous peoples as such mechanisms are very fragmented and practically challenges.